Pengembangan Instrumen Penilaian Aspek Kognitif Berbasis Media Audio Pada Materi Teks Negosiasi Siswa Kelas X SMA - Maya Wardani; Rita; Rika Kartika (Medan Resource Center, 2022)
This study aims to develop and test the feasibility of an audio media-based cognitive aspect assessment instrument for negotiating text material for class X students of SMA Bhayangkari 1 Medan based on research from material expert validators and design experts. The total population of students is 79 students and the sample taken is 25 students, namely class X MIA 1. The source of data in this study is a questionnaire. The data collection techniques used in this study were observation and interviews. This type of research is 4-D research and development by Thiagarajan which consists of four stages, namely define, design, development, and dissemanitoin. The results of this study indicate that the audio media-based cognitive aspect assessment instrument on the negotiating text material for class X SMA students has met the good category. The assessment of the level of validity of the audio media-based cognitive aspect assessment instrument by material experts obtained an overall average of 84% with the criteria